Deep coal mining and meningococcal meningitis in England and Wales, 1931–38: ecological study, with implications for deep shaft mining activities worldwide - Smallman-Raynor, Matthew R.; Cliff, Andrew D. (Elsevier, 2017)
The hypothesized role of deep coal mining in the development of community-based outbreaks of meningococcal meningitis has gone largely unexplored. Taking the coalfields of Britain as a historical testbed, techniques of linear and binomial logistic regression were used to assess the association between meningococcal meningitis rates and male occupation rates for coal mining in England and Wales during the national epidemic of 1931–32 and in its aftermath. Adjusting for the epidemiological effects of age, residential density, recent changes in the number of families, housing stock and low social class, the analysis yielded evidence of a significant and positive association between coal mining occupation rates and notified levels of meningitis activity in the epidemic period. Communities in areas of the world that currently maintain substantial deep coal extraction industries may be at increased risk for the epidemic transmission of meningococcal meningitis.